1997
DOI: 10.1046/j.1365-2141.1997.d01-2137.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Smoking on the Fibrinolytic Potential of Plasma and Platelets

Abstract: Summary.We studied tissue-type plasminogen activator (t-PA) and plasminogen activator inhibitor type 1 (PAI-1) in healthy individuals divided by smoking habit into current smokers, former smokers and non-smokers (who had never smoked). Plasma PAI-1 antigen was significantly higher in smokers than in non-smokers with intermediate levels in former smokers. A similar trend was observed for plasma PAI activity but this did not reach statistical significance. Platelet PAI-1 and plasma t-PA were not significantly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 23 publications
4
39
0
3
Order By: Relevance
“…10,17 Also chronic smoking has been associated with impaired fibrinolysis in plasma and this largely reflected elevated plasma PAI-1 in smokers. 14 It is interesting that the genetic association of the functional promoter polymorphism in the PAI-1 gene with periodontitis in our study was observed only in the group of non-smokers. The impairment of the fibrinolytic mechanisms in smokers may occur as a consequence of smoking which is known to increase the levels of PAI-1, thus possibly masking the influence of individual variants of the PAI-1 polymorphism.…”
Section: Genes and Immunitymentioning
confidence: 52%
See 1 more Smart Citation
“…10,17 Also chronic smoking has been associated with impaired fibrinolysis in plasma and this largely reflected elevated plasma PAI-1 in smokers. 14 It is interesting that the genetic association of the functional promoter polymorphism in the PAI-1 gene with periodontitis in our study was observed only in the group of non-smokers. The impairment of the fibrinolytic mechanisms in smokers may occur as a consequence of smoking which is known to increase the levels of PAI-1, thus possibly masking the influence of individual variants of the PAI-1 polymorphism.…”
Section: Genes and Immunitymentioning
confidence: 52%
“…10 PAI-1 than those with one or two copies of the 5G allele; 10 the 5G allele is characterized by a lower transcriptional rate of the PAI-1 gene because of binding a transcriptional repressor protein which cannot be bound by the 4G allele. 10,12 Since the 4G allele of the 4G/5G promoter polymorphism of the PAI-1 gene and/or smoking have been previously associated with increased plasma levels and activity of PAI, 13,14 we investigated the role of this polymorphism in the pathogenesis of adult periodontitis with regard to smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…1 Smoking acts synergistically with other vascular risk factors (eg, hypertension, dyslipidaemia and diabetes) to increase vascular morbidity and mortality. 2 However, smoking has a variable magnitude of increased risk for different vascular diseases: the risk is highest for peripheral arterial disease and aortic aneurysm, and is lowest for coronary artery and cerebrovascular diseases.…”
mentioning
confidence: 99%
“…Результаты, полученные в много-численных наблюдательных когортных, эксперименталь-ных и лабораторных исследованиях на людях и животных [225,[227][228][229], выявили механизмы влияния курения на эндотелиальную функцию [230,231], окислительные процессы [232], функцию тромбоцитов [233], фибринолиз, воспаление [234][235][236][237][238], вазомоторную функцию и модифи-кацию липидов . Активные формы кислорода -свободные радикалы -находящиеся во вдыхаемом дыму являются причиной окисления ЛПНП в плазме крови; окисленные ЛПНП, стимулируют процессы воспаления за счет прили-пания моноцитов к стенке сосудов, что является пусковым механизмом воспалительных изменений в интиме артерий, который приводит к прогрессированию атеросклероза [232,[239][240][241][242] .…”
Section: механизм увеличивающий риск от куренияunclassified